Ethnobotany of Medicinal Plants in the Wasilomata Cluster Community, Mawasangka District, Central Buton Regency, Southeast Sulawesi Province - Maretik, Maretik; Alimuddin, Alimuddin; Saparuddin, Saparuddin (ITScience (Information Technology and Science), 2023)
Ethnobotany is a botanical science that studies the use of plants in everyday life which are used by certain ethnicities or tribes, and are passed down from generation to generation. The aim of this research is to determine the types and parts of medicinal plants used as well as how to process and utilize medicinal plants in the Wasilomata grove community, Mawasangka District, Central Buotn Regency, Southeast Sulawesi Province. This research is a qualitative descriptive research using several methods, namely observation, interviews, documentation, plant identification. The interview method was carried out using purposive sampling technique. The subjects in this research were youth leaders, traditional leaders, community leaders and healers. The results of the interview stated that there are 50 types of medicinal plants that are often used in the Wasilomata Grove. The parts of plants used as medicine are leaves, stems, fruit, roots, rhizomes, seeds and tubers. The way to process plants as medicine is boiling, pounding, squeezing, grating and splitting. Meanwhile, its users can treat 19 diseases, namely external wounds, high blood pressure, fever, cholesterol, coughs, boils, malaria, diarrhea, eye pain, serampa, burns, itching, toothache, poisoning, kidney stones, gout, acne, rheumatism and diabetes. It was concluded that there are 50 species of medicinal plants. The part of the plant most widely used as medicine is the leaves (70%). The most widely used method of processing plants as medicine is by boiling (46%) and the use of plants that are mostly used to treat external wounds (20%).